CSR initiative characteristics and employee engagement: An impact‐based perspective. (10th April 2018) - Opoku‐Dakwa, Akwasi; Chen, Chao C.; Rupp, Deborah E.
Summary: Though corporations depend on the work of employees to achieve important humanitarian and environmental outcomes, research on employee engagement in corporate social responsibility initiatives (CSRIs) remains limited and fragmented. Building on existing studies, we develop a theoretical model explaining when and why CSRIs, on the basis of their distinctive characteristics, would be engaging to employees. Adopting the lens of social cognitive theory, we position employees as potential agents of social change, whose efforts are enabled through CSRIs that are expected to meaningfully impact stakeholders (including the employees themselves, their employing organizations, and external beneficiaries). We first model CSRIs in terms of their focus characteristics, which reflect the different types of goals that CSRIs can have. We then explain how these CSRI characteristics promote employee engagement through anticipated impacts that are commensurate with employees' personal expectations. Lastly, we explain how these effects depend on organizational support for the CSRI, which shapes employees' beliefs about the collective efficacy of the organization to achieve the CSRI goals, and on employees' identities, which determine the types of CSRI impacts that are more meaningful and therefore more conducive to engagement. We conclude with a discussion of implications for research and practice.